2017
DOI: 10.1002/jssc.201700817
|View full text |Cite
|
Sign up to set email alerts
|

l‐Cysteine‐modified silver‐functionalized silica‐based material as an efficient solid‐phase extraction adsorbent for the determination of bisphenol A

Abstract: A new silver-functionalized silica-based material with a core-shell structure based on silver nanoparticle-coated silica spheres was synthesized, and silver nanoparticles were modified using strongly bound l-cysteine. l-Cysteine-silver@silica was characterized by scanning electron microscopy and FTIR spectroscopy. Then, a solid-phase extraction method based on l-cysteine-silver@silica was developed and successfully used for bisphenol A determination prior to HPLC analysis. The results showed that the l-cystein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Balamurugan et al [ 78 ] investigated the effects of operating parameters, such as gas velocity, liquid level in the suction chamber, nozzle diameter, and throat diameter on the mass transfer characteristics of gas–liquid ejectors. In addition, an increase in the nozzle velocity and power input per unit volume (P/V) had shown a positive impact on the mass transfer coefficient and interfacial area.…”
Section: Modification Of Reactor Designmentioning
confidence: 99%
“…Balamurugan et al [ 78 ] investigated the effects of operating parameters, such as gas velocity, liquid level in the suction chamber, nozzle diameter, and throat diameter on the mass transfer characteristics of gas–liquid ejectors. In addition, an increase in the nozzle velocity and power input per unit volume (P/V) had shown a positive impact on the mass transfer coefficient and interfacial area.…”
Section: Modification Of Reactor Designmentioning
confidence: 99%
“…It has been reported that either ethanol solution (75%) or ammonium hydroxide solution (0.5 M) is capable of desorbing BPA off carbon adsorbents [36]. Indeed, the BPA recovery rate increased with increasing solvent polarity, indicating a stronger interaction with BPA when the number of available polar sites in the solvent molecule became greater [39]. At pH ≤ 8, most of the BPA (pK a 9.7) present is neutral, resulting in decreased binding.…”
Section: Introductionmentioning
confidence: 99%